Lugares da memória: a vivência da migração nordestina no interior paulista entre avós e netos - Silva, Cinthia Xavier da [UNESP] (2014)
In the mid 20th century an expressive internal migration took place in Brazil, mostly from the Northeast of the country to the industrial capitals of the Southeast, but also to small new towns in the State of São Paulo. We examine here the narratives of this important but often overlooked migration as they are told by the migrating families that settled in Barbosa, a city that sprang from a late 19th century settlement located 300 miles from the cap ital. Through extensive field research and interviews with “Nordestinos” who migrated in the 1930s, 40s and 50s, their children and grandchildren, including the family of the researcher herself, we examine how migration narratives are transmitted between generations in what we are calling “places of memory”: situations created by the migrating grandparents or inherited from Northeastern traditions in which the past in the place of origin is remembered, the migration itself is recalled and, above all, a certain way of being and acting is taught to the younger generation. Among the places of memory we identified are family gatherings around life cycle events; public gatherings where fathers and grandfathers publicly tell stories about characters collectively known; domestic spaces where mothers and grandmothers make sense of the family history; religious festivities such as “Festas Juninas” and “Terços” taking place in June and July; the fantastic realm of stories where mystic beings and animals relate to human beings; and, last but not least, the forms of media that supported memories and narratives in this strongly oral culture (such as photographs and wall portraits kept during the migration or sent back and forth by mail to relatives in the Northeast). In spite of the important role migration narratives and their attached teachings have for this community, we noticed that they and their context are largely absent from public school de facto curriculum. Basic education...